2013
DOI: 10.5142/jgr.2013.37.379
|View full text |Cite
|
Sign up to set email alerts
|

Heat-processed Panax ginseng and diabetic renal damage: active components and action mechanism

Abstract: Diabetic nephropathy is one of the serious complications in patients with either type 1 or 2 diabetes mellitus but current treatments remain unsatisfactory. Results of clinical research studies demonstrate that Panax ginseng can help adjust blood pressure and reduce blood sugar and may be advantageous in the treatment of tuberculosis and kidney damage in people with diabetes. The heat-processing method to strengthen the efficacy of P. ginseng has been well-defined based on a long history of ethnopharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 77 publications
2
67
0
1
Order By: Relevance
“…Panax Ginseng in general has been shown to have antioxidant and anti-inflammatory effects (Lee and Son, 2011). Also recent studies have provided a great support for evidencing the protective effects of ginseng on kidney damage (Kang et al, 2013). In our investigation, ginsenoside Rb1+Se and ginsenoside Rb1 treated groups showed an improvement in kidney function tests when compared with control.…”
Section: Discussionsupporting
confidence: 59%
“…Panax Ginseng in general has been shown to have antioxidant and anti-inflammatory effects (Lee and Son, 2011). Also recent studies have provided a great support for evidencing the protective effects of ginseng on kidney damage (Kang et al, 2013). In our investigation, ginsenoside Rb1+Se and ginsenoside Rb1 treated groups showed an improvement in kidney function tests when compared with control.…”
Section: Discussionsupporting
confidence: 59%
“…With regard to the reason of the anti‐oxidative properties of KRG against CsA toxicity, it also requires the components of KRG associated with anti‐oxidative effect. Based on the previous reports, Rg1, Re, Rb1, and Rd are suggested as main the components of ginseng containing anti‐oxidative effects in kidney disorders . These components were evaluated to have therapeutic potential against renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous reports, Rg1, Re, Rb1, and Rd are suggested as main the components of ginseng containing anti-oxidative effects in kidney disorders. 31 These components were evaluated to have therapeutic potential against renal disease. KRG used in this study contains all of these components, so we can speculate that Rg1, Re, Rb1, and Rd might be associated with an active form of anti-oxidative effect against CsA-induced renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…PG exhibits anticancer, 6 anti‐aging, 7 immunity‐enhancing, 8 antidepressant, 9 and antidiabetic properties 10 . The pharmacological activities of PG have been mainly attributed to the ginsenoside compounds, 11–16 although polysaccharides are also major bioactive components of PG 17,18 . Recently, it was reported that ginseng polysaccharides enhanced the absorption of ginsenoside Rb 1 and the exposure of microbial metabolites 19 .…”
Section: Introductionmentioning
confidence: 99%